First-in-Human Experience With Transcatheter Mitral Valve-in-Valve Implantation During Left Ventricular Assist Device Placement. (November 2016) - Orasanu, Gabriela; Al-Kindi, Sadeer G.; Robinson, Monique R.; Oliveira, Guilherme H.; Ginwalla, Mahazarin; Elamm, Chantal; Zacharias, Michael; Farhoud, Mahmoud; Medalion, Benjamin; Deo, Salil V.; Park, Soon J.; Attizzani, Guilherme F.; et al.
Abstract : Supplemental Digital Content is available in the text.